2004
DOI: 10.1002/mrd.20091
|View full text |Cite
|
Sign up to set email alerts
|

Blastocysts produced by nuclear transfer between chicken blastodermal cells and rabbit oocytes

Abstract: Interspecies nuclear transfer (INT) has been used as an invaluable tool for studying nucleus-cytoplasm interactions; and it may also be a method for rescuing endangered species whose oocytes are difficult to obtain. In the present study, we investigated interaction of the chicken genome with the rabbit oocyte cytoplasm. When chicken blastodermal cells were transferred into the perivitelline space of rabbit oocytes, 79.3% of the couplets were fused and 9.7% of the fused embryos developed to the blastocyst stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
2
23
1
Order By: Relevance
“…Our results were not different from several other recent reports (Chung et al 2009, Lagutina et al 2010, who had also reported that iSCNT embryos failed to reactivate the embryonic genome and arrested at the stage of EGA specific to the recipient oocyte. Conversely, inter-genus (Oh et al 2006, Yin et al 2006, inter-family (Dominko et al 1999, Zhao et al 2007, inter-order (Yang et al 2003, Wen et al 2005, Illmensee et al 2006, and even inter-class iSCNT (Chen et al 2002, Liu et al 2004 nuclear transfer embryos were reported to have Pig-mouse cytoplasmic hybrid embryos developed to the blastocyst stage. However, these later reports also observed that the majority of iSCNT embryos arrested around the stage of EGA and only a very small percent of embryos developed to blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were not different from several other recent reports (Chung et al 2009, Lagutina et al 2010, who had also reported that iSCNT embryos failed to reactivate the embryonic genome and arrested at the stage of EGA specific to the recipient oocyte. Conversely, inter-genus (Oh et al 2006, Yin et al 2006, inter-family (Dominko et al 1999, Zhao et al 2007, inter-order (Yang et al 2003, Wen et al 2005, Illmensee et al 2006, and even inter-class iSCNT (Chen et al 2002, Liu et al 2004 nuclear transfer embryos were reported to have Pig-mouse cytoplasmic hybrid embryos developed to the blastocyst stage. However, these later reports also observed that the majority of iSCNT embryos arrested around the stage of EGA and only a very small percent of embryos developed to blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
“…Once being set off, the program can also act on genomes, which might have various origins and specifications, by converting their epigenetic features into embryo specific state, or in other words -reprogramming them. This ability allows different manipulations with the zygote such as the creation of parthenogenetic (monoparental) embryos, and nuclear/pronuclear transfer, including interspecies transfer (Chang et al, 2003;Hammer et al, 2001;Liu et al, 2004b;McGrath and Solter, 1983;McGrath and Solter, 1984;McGrath and Solter, 1986). The mature oocyte, awaiting the fertilization at metaphase II, gets activated by the penetrating sperm, but it also can be artificially activated in vitro by chemicals, or even by temperature and pH shifts (Meo et al, 2004;Nagai, 1987;Prather et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…When exploring the development of cloned embryos derived from transgenic common carp (Cyprinus carpio) nuclei and goldfish (Carassius auratus) enucleated eggs, we also found that the mtDNA of donor and receptor co-existed in the cloned embryos before blood-circulation (Sun et al 2005). Not come singly but in pairs, the same phenomenon was found in inter-species cloned embryos, such as chicken-rabbit cloned embryos (Liu et al 2004). In our ongoing studies, G.M COXI and Z.M COXI is used not only to analyze the mtDNA heteroplasmy in the cloned embryos derived from the nuclei of G. rarus and the enucleated eggs of D. rerio, but also to track the destiny of donor-derived mtDNA.…”
Section: Disscussionmentioning
confidence: 74%